Understanding team mental models affecting Kaizen event success. Issue 7 (12th October 2015) - Liu, Wen-Hsing; Asio, Sarah; Cross, Jennifer; Glover, Wiljeana J.; Van Aken, Eileen
Abstract : Purpose: – The purpose of this study is to identify inhibitors and enablers of Kaizen event effectiveness, as perceived by participants, and categorize them into shared mental models to understand the factors participants believe to be affecting Kaizen event success. The findings are also interpreted using the lens of attribution bias and previous studies of Kaizen event effectiveness. Design/methodology/approach: – A qualitative approach involving coding responses from participants was adopted. The identified significant inhibitors and enablers were then assigned to shared mental model types using a mapping and categorization approach. Findings: – The results are largely consistent with previous studies and show that job/task and technology/equipment mental models dominate participant views of inhibitors, while enablers were primarily drawn from team and team interaction mental models. This also suggests that attribution bias is present. Research limitations/implications: – The methods used to measure shared mental models in this study are cross-sectional and exploratory in nature. Future research could involve the intensive study of a smaller number of Kaizen events over time. Practical implications: – The findings in this study can be used by organizations to identify training needs for Kaizen event teams by identifying areas of potential attribution bias, by divergence of perceptions between facilitators and team members and by underestimated factor effects. Originality/value: – This investigation offers understanding of the Kaizen event team shared mental models with respect to inhibitors and enablers of event success. Organizations can harness common perceptions among continuous process improvement teams to increases chances of Kaizen event success.